Pengembangan Pembelajaran Bolabasket Melalui Permainan Lumba Jaring (Department of Physical Education, Sport, Health and Recreation, 2016)
The purpose of research to produce a basketball learning model with lumba jaring games atseventh grades students of SMPN 2 Talang Tegal Regency 2015 in the physical educationlearning. The methods of research is procedural development research, The data analysistechnique used is deskriptif presentase. From the test results obtained expert evaluation ofdata are, experts of physical education 90.53% (good), expert’s of learning I 90% (good), expertsof learning II 88% (good), small group trial 84,95% (good), the field test 89.35% (good).from the data, it can be conclude learning model through lumba jaring games can be used forstudents of SMP Negeri 2 TalangTegal. Based on the result, lumba jaring games can be usedin the process of sport learning.